The Use of Indonesian Slang by Makassar Families in Their Daily Interaction - Jabri, Umiyati; Samad, Ita Sarmita (Universitas Muhammadiyah Enrekang, 2019)
This research was aimed at finding out the kind of Indonesian slang that is used by Makassar family in their daily interaction. Indonesia slang’s called bahasa gaul (the 'social language'), where bahasa means 'language' and gaul means 'social', 'cool' or 'trendy'. Indonesian slang is predominantly used in everyday conversation, social milieus, among popular media and, to a certain extent, in teen publications or pop culture magazines. The researchers employed descriptive research method.. The researcher took the audio recordings, wrote the transcript of conversation, and analysing the extract of conversation .The researchers took their own family as the subject of the research. The result showed most of Makassar family use Indonesian slang in their daily interaction. They are rare use Indonesian formal language when they speak with the others family member. There are two kinds of Indonesian slang which is always used by them, namely Jakarta slang and Makassarese slang.